Peningkatan Penguasaan Mufradat Bahasa Arab dengan Media Gambar pada Siswa Kelas XI I MA As-Sunniyyah Kencong Jember - Furoidah, Asni; Jum’ah, Masruroh Lailatal (INAIFAS Press, 2023)
Arabic is a language that we need to learn, as it is important for Muslims to understand the Qur'an and hadith. To understand it, you must memorize Arabic mufrodat first. In reality on the ground, not a few of the class XI I MA Assunniyyah students have difficulty in mastering mufrodat. The use of image media can help make it easier for students to improve their vocabulary. The purpose of this study was to assist class XI.I students in improving their mastery of Arabic mufrodat with the help of picture media. This research is a qualitative research because the object of research is focused on increasing the mastery of Arabic mufrodat using image media. The results showed that female students were more dominant in getting an A score compared to students who got less B and C grades. The results of this research indicate that image media can be used to improve the Arabic mufrodat mastery of class XI I MA As-Sunniyyah Kencong Jember students.